Early steroid withdrawal has a positive effect on bone in kidney transplant recipients: a propensity score study with inverse probability-of-treatment weighting. (October 2020) - Batteux, Benjamin; Gras-Champel, Valérie; Lando, Mathilde; Brazier, François; Mentaverri, Romuald; Desailly-Henry, Isabelle; Rey, Amayelle; Bennis, Youssef; Masmoudi, Kamel; Choukroun, Gabriel; Liabeuf, Sophie
Background: Long-term corticosteroid use after kidney transplantation is associated with a decrease in bone mineral density (BMD) and a high fracture risk. We hypothesized that patients with early steroid withdrawal (ESW) would display a gain in BMD in the year following kidney transplantation, when compared with patients on long-term corticosteroid therapy. Methods: In a cohort of kidney transplant recipients, 356 patients were included between 2012 and 2019. Dual-energy X-ray absorptiometry was performed 1 and 12 months after transplantation. The data were analyzed using linear regression with inverse probability-of-treatment weighting (based on a propensity score). Results: At 1 year after transplantation, the gain in BMD was significantly greater in recipients with ESW than in recipients on long-term corticosteroid therapy for the lumbar spine (+0.036 g/cm 2, p  < 0.001) and the femoral neck (+0.020 g/cm 2, p  = 0.035). Among patients with ESW, (i) none had osteoporosis, (ii) the percentage with normal BMD increased from 33.3% at month 1 to 54.4% at month 12, and (iii) the percentage with osteopenia fell from 56.2% to 45.6%. In patients undergoing long-term corticosteroid therapy, the fracture incidence was 13.5 per 1000 person-years. None of the patients in the ESW group experienced a fracture. Conclusion: ESW has a positive effect on bone in kidney transplant recipients.